2014
DOI: 10.7567/jjap.53.111302
|View full text |Cite
|
Sign up to set email alerts
|

Inclination of a threading dislocation in an epilayer of 4H-SiC

Abstract: Threading dislocations (TDs) are inclined from the [0001] c-axis in 4H-SiC epilayers which are produced by the step-controlled technique. The reason for this inclination is discussed in the framework of isotropic elastic theory of dislocation. The elastic strain energy of a TD in an epilayer is calculated as a function of its orientation, and the minimum energy orientation is used to predict the inclination angle. The results of the calculations are as follows. For a cut-off angle (α) of 4°, a threading edge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Saka et al. also reported that the strain energy of dislocations in the epitaxial layer affects the inclined direction of the dislocations of a TD in SiC . Figure shows a schematic diagram of the dislocation inclination model.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Saka et al. also reported that the strain energy of dislocations in the epitaxial layer affects the inclined direction of the dislocations of a TD in SiC . Figure shows a schematic diagram of the dislocation inclination model.…”
Section: Resultsmentioning
confidence: 98%
“…Figure shows a schematic diagram of the dislocation inclination model. The strain energy ( W E ), when a TD is inclined toward the direction b in the epitaxial layer, is expressed as followsWnormalEb2ln(db)4π(1ν)(1ν(cosαsinγ+sinαcosγ)2)dcosαwhere d is the thickness of the epitaxial layer, ν is the Poisson's ratio, α is the angle of TD from the growth direction, and γ is the angle formed by the growth plane of the epitaxial layer and b . The value of α that minimizes W E is then determined.…”
Section: Resultsmentioning
confidence: 99%
“…TSDs with an inclined angle close to 30°from 〈0001〉 have been theoretically suggested to exist. 12) The propagation of the inclination of TSD from the c-axis was ascertained to be related to the direction of the extra half plane with an a-component by 2PPL. 30) Shinagawa et al 31) estimated that TSD with [1213]/3 of the Burgers vector b had an inclined angle of 26.5°towards the b direction from the c-axis.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] In terms of isotropic elastic principle, TSD with an inclination of dislocation core-line was predicted to be mixed with either 〈1120〉 (a-) or 〈1100〉 (m-) component. 12) TSDs with only the c-component and including a mixed component were categorized as threading pure screw dislocation (TpSD) and threading mixed dislocation (TMD), respectively. However, our understanding of the relationship between the inclination and mixed component in TSD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Recently, inclination angle (θ) of TD from the c-axis to the direction of the dislocation line has been recognized as an attractive candidate to distinguish the harmful TD, because electrical properties of TDs are supposed to be almost decided with their Burgers vector (b) and the θ can be calculated as minimum energy state based on the elastic theory in a crystal from b. [23][24][25][26][27] In general, however, it is considered that θ of a particular TD is resulting from motion of a lot of the other dislocations under internal stress in an epitaxial layer during growth where influence of surface cannot be ignored. 5,22) In this study, we fabricated SiC-IGBTs with a considerably thick layer on a 4H-SiC substrate.…”
Section: Introductionmentioning
confidence: 99%